Modelo numérico do terreno obtido por diferentes métodos em cartas planialtimétricas - Barbosa, Ana P. [UNESP]; da Silva, Alessandra F. [UNESP]; Zimback, Célia Regina Lopes [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2012)
The digital elevation model is important to determine the slope and land use capability, therefore, a proposal of methodology for acquisition of elevation data contemplating an efficient algorithm to generate a slope map was developed. Thus, it was aimed to obtain and evaluate a digital elevation model without the vetorization of the contours on planialtimetric charts. The area for acquisition of elevation data was Sao Manuel, SP. The data were collected by two methods: level contour vetorization and the gathering of elevation points on the level contour with maximum elevation points. The elevation data were analyzed by geostatistical techniques. Inspite of wide difference in the number of collected points between two methods, the variograms were adjusted to the exponential model and showed a range of approximately 1500 m, which does not justify the wide difficulty in vetorization of the planialtimetric charts, once the data points collected in the area were appropriately distributed, they represented rightly the terrain surface.
Digital terrain model obtained by different methods in planialtimetric charts
Keywords: interpolation; kriging; slope